2020
DOI: 10.1177/0333102420951505
|View full text |Cite
|
Sign up to set email alerts
|

Age-related features in vestibular migraine onset: A multiparametric analysis

Abstract: Background Clinical heterogeneity is a peculiarity of vestibular migraine, in contrast to other vestibular disorders that have a more stereotypical expression. Migraine presents a range of variability in symptoms depending on the age of the patient. Supposing that migraine headache and vestibular migraine share the same pathogenetic mechanisms, a multiparametric analysis was performed to verify the hypotheses of an age-related influence on the clinical features of vestibular migraine at the onset. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…These are the same central neurotransmitters in the processes of anxiety and depression [ 26 ]. Furthermore, among the symptoms indicated in the diagnostic criteria of VM, visually induced vertigo has a significant impact in terms of frequency and symptomatology, even considering the high pleomorphism of this pathology [ 17 , 27 ]. A core of symptoms is common between VM and PPPD.…”
Section: Discussionmentioning
confidence: 99%
“…These are the same central neurotransmitters in the processes of anxiety and depression [ 26 ]. Furthermore, among the symptoms indicated in the diagnostic criteria of VM, visually induced vertigo has a significant impact in terms of frequency and symptomatology, even considering the high pleomorphism of this pathology [ 17 , 27 ]. A core of symptoms is common between VM and PPPD.…”
Section: Discussionmentioning
confidence: 99%
“…In all three of our multiple linear regression models investigating age, sex, and history of psychiatric disorders, VM-PATHI was a statistically significant predictor of daily dizziness severity and superior at capturing daily dizziness than the DHI. Age has been linked with an increased incidence of spontaneous dizziness in vestibular migraineurs (18), and this may explain the reason age was a significant predictor of daily dizziness in two of our models. Despite the female predominance in the VM population and the high comorbidity of psychiatric disorders in individuals who experience dizziness (1,19), neither biological sex nor a history of anxiety/depression predicted daily dizziness.…”
Section: Discussionmentioning
confidence: 78%
“…The type of vestibular symptoms varies according to the age of onset of VM. This conclusion may have been limited by the sample size and the investigators set a temporal cut-off of 60 years old, based on the evidence of the radical decrease in the onset of migraine attacks from the age of 50 ( Ori et al, 2020 ). Furthermore, this study also found that patients with pVM had a higher rate of motion sickness, 72.04%, compared to 51.06% of patients in the cVM group and 23.00% in the control group.…”
Section: Discussionmentioning
confidence: 99%